2016
DOI: 10.1002/adfm.201600780
|View full text |Cite
|
Sign up to set email alerts
|

In‐Plane Self‐Turning and Twin Dynamics Renders Large Stretchability to Mono‐Like Zigzag Silicon Nanowire Springs

Abstract: Crystalline Si nanowire (SiNW) springs, produced via a low temperature (<350 °C) thin fi lm technology, are ideal building blocks for stretchable electronics. Herein, a novel cyclic crystallographic-index-lowering self-turning and twin dynamics is reported, during a tin-catalyzed in-plane growth of SiNWs, which results in a periodic zigzag SiNW without any external parametric intervention. More interestingly, a unique twin-refl ected interlaced crystaldomain structure has been identifi ed for the fi rst time, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 36 publications
(58 reference statements)
1
37
0
Order By: Relevance
“…The in-plane NWs could be used as building blocks for nanooptical and nanoelectronical devices, 31 as well as for stretchable electronics. 32 The planar growth mode could be easily transformed into vertical one by a proper choice of laser plasma energies.…”
Section: Results and Discussionmentioning
confidence: 99%
“…The in-plane NWs could be used as building blocks for nanooptical and nanoelectronical devices, 31 as well as for stretchable electronics. 32 The planar growth mode could be easily transformed into vertical one by a proper choice of laser plasma energies.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Note that the time-varying bends (up and down) of the end of the nanowire with [112]-orientation ( Fig. 6A) during its contraction can be due to the same physical factors that lead to periodic deviations in the direction of growth of the synthesized nanowire away from the general Si [112]-direction 70 .…”
Section: Discussionmentioning
confidence: 99%
“…For SiC NWs, they usually contain well-developed cubic (3C) structured segments, stacking faults, and also H-type structured segments and even helical structure 17 , dramatically affecting their mechanical properties, that may be the reason why the Young's modulus of SiC NWs vary widely 18 . Recently, reserachers demonstrated that the stretchability of traditional brittle materials can be enhanced by buckling and channel guiding strategy [19][20][21][22] . Besides the structure mentioned above, one-dimentional disordered (ODD) structure with high density defects is another ubiquitous structure not only in SiC but also in other materials 8,23,24 , the symmetry and periodicity of the original face-centered cubic structure of SiC in the ODD structure change thoroughly 8 , which is considered to have not only great effect on mechanical properties but also on catalytic performance 24 .…”
Section: Xuejiao Zhang 13 Jing Wang 13 Zhenyu Yang 23 Xuke Tmentioning
confidence: 99%